Pengaruh Motivasi Spiritual dan Disiplin Kerja terhadap Kinerja Karyawan - Irma Idayati (IPM2KPE, 2019)
The purpose of this study was to determine the effect of spiritual motivation and work discipline on the performance of PT. DendymarkerIndahlestari. This study uses a quantitative approach that uses questionnaires in data collection techniques. To do the hypothesis test used simple regression techniques, simple correlation, multiple regression, coefficient of determination, t test and F test. All the analysis process, in its calculation is assisted with the application of SPSS 20.0. The results of the study, simultaneously the variables of spiritual motivation (X1) and work discipline (X2) on employee performance showed value, Fcount obtained was 39.565>Ftable = 3.30 and the significance level simultaneously significance was 0,000 <(α) = 0.05 df = n - k = 37 - 2 - 1 = 34 is equal to 3.28 so that Ho is rejected and Ha is accepted. the meaning shows that together (simultaneously) the independent variables, namely spiritual motivation and work discipline have a significant influence on the dependent variable, namely employee performance, so that the truth is proven and the hypothesis is acceptable. Conclusion, there is an influence of spiritual motivation and work discipline on employee performance. Keywords: Spiritual Motivation, Work Discipline, Employee Performance